(3QSGFd GHf GdYejOs - (3eMeO Hf GdMSjf GdYejO Hf eMeO, CHh GdaVd,J (B360 (3g` s
(3ChdgG (B:s
(3CeG HYO , agPg QSGFd GdUOQ GdEeGe aefgG QSGdI cJHgG Edi HYV CUObGFg GdeWHNjI, cJHgG HGdQbI jYQV HUOjb dg ZjQ GdecJhH Edjg s
(3BNQgG (B:s
(3hdg cJGH hYjO Edi MSGf Hf LQGM deG fgH GdQedI hNGda GdOhdI(B: (3dbO ef Ydjc CejQ GdeDefjf eQI CNQi hEf MQeJ gG QCjJ ShA UHGMc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B257s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdhWfjg cdcJG (B((3eLehYI HgGQ (B412) s
Keywords: (3GdCOHs